Konsep Al-Ukhuwah dalam Al-Qur'an (Studi Tafsir Tematik) - Sri Nilawati; Mardan; Muhammad Sadik (CV Putra Publisher, 2024)
Brotherhood in the Qur'an is a bond of brotherhood caused by similarities in various aspects, such as descent, ethnicity, religion, profession and character, which forms an inner bond so that each other feels close. Even though they are different people and have different beliefs, the Koran explains that all people are brothers. In the Al-Quran there are several types of ukhuwwah, including Ukhuwah 'ubudiyah which states that all who are created as creatures have a sibling relationship. Ukhuwah Insaniyah that all humans are brothers, because all humans originate from one father and mother, namely Adam and Eve. Ukhuwah Wathaniyah wa Nasabiyah that, Brothers in one lineage and one nationality. Ukhuwah Fiddin wal Islam means, sibling relationships between fellow Muslims